Analyses of Bone Regeneration Capacity of Freeze-Dried Bovine Bone and Combined Deproteinized–Demineralized Bovine Bone Particles in Mandibular Defects: The Potential Application of Biological Forms of Bovine-Bone Filler - Kamadjaja, David Buntoro; Satriyo, Handhito; Setyawan, Aris; Lesmaya, Yeni Dian; Safril, Jefry Wahyudi; Sumarta, Ni Putu Mira; Rizqiawan, Andra; Danudiningrat, Coen Pramono; Tran, Ta To (European Journal of Dentistry, 2021)
Objective This study aimed to evaluate bone regeneration capacity of FDBX granules compared to composite DBBM/DFDBX granules for filling of bone defect in rabbit mandible.Material and Methods Critical size defects were created in 45 rabbits' mandible. The defect in the control group is left untreated, while in other groups the defects were filled with FDBX granules and composite DBBM/DFDBX granules, respectively. Specimens were collected at 2, 4, and 8 weeks for histology and immunohistochemical analyses. Significant difference is set at p-value < 0.05.Results The osteoblast-osteoclast quantification, osteoblast expression of Runx2, alkaline phosphatase, collagen-I, and osteocalcin, and osteoclast expression of receptor activator of NF-kB ligand (RANKL) and osteoprotegerin (OPG) in FDBX groups were statistically comparable (p > 0.05) with the composite group, while OPG/RANKL ratio, bone healing scores, and trabecular area were significantly higher (p < 0.05) in the composite compared to FDBX group.Conclusion Composite DBBM/DFDBX granules, within the limitation of this study, has better bone forming capacity than FDBX granules for filling of bone defects in the mandible.
Keywords: bovine; deproteinized; demineralized; osteoconductive; osteoinductive; bone filler; innovation